2019
DOI: 10.3390/atmos10110680
|View full text |Cite
|
Sign up to set email alerts
|

Dust Heterogeneous Reactions during Long-Range Transport of a Severe Dust Storm in May 2017 over East Asia

Abstract: Dust aerosol has important climate and environmental effects, which could be changed by internally mixing with anthropogenic aerosol as a result of heterogeneous reactions; however, the importance of these reactions is not fully understood yet. In this study, synergetic observations and an air quality model were used to analyze the transport of a severe dust storm and its impacts on nitrate and sulfate levels over East Asia between 3 and 11 May 2017. The model successfully reproduced the occurrence and transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) based on the CALIPSO satellite, provide dust altitude and layer thickness information [22]. In addition, multispectral radiometers can outline dust plume evolution, e.g., the geostationary satellite HIMAWARI 8 RGB imager [23] and the Moderate Resolution Imaging Spectroradiometer (MODIS), which also differentiates natural dust from anthropogenic dust with lower Aerosol Optical Depth (AOD) values [24]. Furthermore, spectrometers with high spectral resolution allow for quantifying aerosol parameters such as the effective radius from the Atmospheric Infrared Sounder (AIRS) [25] and the Infrared Atmospheric Sounding Interferometer (IASI) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) based on the CALIPSO satellite, provide dust altitude and layer thickness information [22]. In addition, multispectral radiometers can outline dust plume evolution, e.g., the geostationary satellite HIMAWARI 8 RGB imager [23] and the Moderate Resolution Imaging Spectroradiometer (MODIS), which also differentiates natural dust from anthropogenic dust with lower Aerosol Optical Depth (AOD) values [24]. Furthermore, spectrometers with high spectral resolution allow for quantifying aerosol parameters such as the effective radius from the Atmospheric Infrared Sounder (AIRS) [25] and the Infrared Atmospheric Sounding Interferometer (IASI) [26].…”
Section: Introductionmentioning
confidence: 99%
“…The HNO 3 can also react with dust and sea salt to form coarse mode nitrate aerosols, and affect the atmospheric nitrogen deposition on the ocean ( Wang et al, 2017b , 2018 ; Z. Wang et al, 2019 , Wang et al, 2019 ). A recent study indicates that nitrate aerosol increased significantly over downwind areas of East Asia in recent years ( Uno et al, 2020 ), implying that the nitrate aerosol is increasing in importance over East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Dust aerosols remain an important environmental pollutant in North China (Zheng et al, 2020). Model simulations have shown that the mass ratio of dust nitrate to dust aerosol can reach 10% over the Pacific Ocean (Wang et al, 2019). It was reported that the Asian dust can be transported at least one full circuit around the globe (Uno et al, 2009).…”
Section: Introductionmentioning
confidence: 99%